Secrets of The lost symbol the unauthorized guide to the mysteries behind the Da Vinci code sequel - Burstein, Daniel 1953-; De Keijzer, Arne (Morrow, 2010)
Dan Burstein and Arne de Keijzer delve into the real history, science, and hidden meanings behind Dan Brown's latest novel, The Lost Symbol. As in their previous books, they explore the themes, conspiracies, mythologies, codes, encrypted signs, and alternate histories--from the birth of Knights Templar to the present day--popularized by the acclaimed creator of The Da Vinci Code, giving them fresh relevance while separating truth from fantasy.--From publisher description